UNATI: rompendo mitos e esteriótipos em relação ao envelhecimento - Dellefrate, Anna Carolina Garcia Tarantini [UNESP] (2015)
This article deals with the integration and social participation of the elderly and how the Open University of the Third Age has broken the myths and stereotypes related to aging and achieved intergenerational interaction, showing how the elderly nowadays are active and conscious subjects of their rights and duties. Emphasizing the achievements in the development of activities in the period of 2015. The execution of the Project is carried out by professors from different areas of knowledge of the internal and external community with different professionals and nursing Dracena and region.